Is Dysregulation of the HPA-Axis a Core Pathophysiology Mediating Co-Morbid Depression in Neurodegenerative Diseases? - Du, Xin; Pang, Terence Y. (Frontiers in Psychiatry, 2015)
There is increasing evidence of prodromal manifestation of neuropsychiatric symptoms in a variety of neurodegenerative diseases such as Parkinson’s disease and Huntington’s disease. These affective symptoms may be observed many years before the core diagnostic symptoms of the neurological condition. It is becoming more apparent that depression is a significant modifying factor of the trajectory of disease progression, and even treatment outcomes. It is therefore crucial that we understand the potential pathophysiologies related to the primary condition, which could contribute to the development of depression. The hypothalamic-pituitary-adrenal (HPA) axis is a key neuroendocrine signaling system involved in physiological homeostasis and stress response. Disturbances of this system lead to severe hormonal imbalances, and the majority of such patients also present with behavioural deficits and/or mood disorders. Dysregulation of the HPA axis is also strongly implicated in the pathology of major depressive disorder. Consistent with this, anti-depressant drugs such as the selective serotonin reuptake inhibitors (SSRI) have been shown to alter HPA axis activity. In this review, we will summarize the current state of knowledge regarding HPA axis pathology in Alzheimer’s, Parkinson’s and Huntington’s diseases, differentiating between prodromal and later stages of disease progression where possible. Both clinical and preclinical evidence will be examined, but we highlight animal model studies as being particularly useful for uncovering novel mechanisms of pathology related to co-morbid mood disorders. Finally, we purpose utilizing the pre-clinical evidence to better inform prospective, intervention studies.